2021
DOI: 10.3390/en14217148
|View full text |Cite
|
Sign up to set email alerts
|

Production and Evaluation of Fractionated Tamarind Seed Oil Methyl Esters as a New Source of Biodiesel

Abstract: Biodiesel has attracted considerable interest as an alternative biofuel due to its many advantages over conventional petroleum diesel such as inherent lubricity, low toxicity, renewable raw materials, biodegradability, superior flash point, and low carbon footprint. However, high production costs, poor low temperature operability, variability of fuel quality from different feedstocks, and low storage stability negatively impact more widespread adoption. In order to reduce production costs, inexpensive inedible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Another report elucidated the enhancement of antioxidative enzyme activities in the liver and kidneys following CoQ supplement in a piroxicam-intoxicated rat (Abdeen et al, 2020). Besides the antioxidant properties, TM and CoQ have antihyperlipidemic (Velu et al, 2018;Gutierrez-Mariscal et al, 2020) and antiinflammatory (Abdeen et al, 2020;Mushtaq et al, 2021;da Silveira e Sá Rde et al, 2015) capabilities, which supposedly play a role in restoring serum cholesterol and triglyceride levels and obscuring lymphocytic infiltrates as indicated in our histopathology results, respectively. There are various mechanisms by which CoQ serves lipid metabolism such as boosting fatty acid oxidation and inhibiting the oxidation of low-density lipoprotein, the primary carrier of blood cholesterol, which is implicated in the cumulation of cholesterol (Gutierrez-Mariscal et al, 2020).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Another report elucidated the enhancement of antioxidative enzyme activities in the liver and kidneys following CoQ supplement in a piroxicam-intoxicated rat (Abdeen et al, 2020). Besides the antioxidant properties, TM and CoQ have antihyperlipidemic (Velu et al, 2018;Gutierrez-Mariscal et al, 2020) and antiinflammatory (Abdeen et al, 2020;Mushtaq et al, 2021;da Silveira e Sá Rde et al, 2015) capabilities, which supposedly play a role in restoring serum cholesterol and triglyceride levels and obscuring lymphocytic infiltrates as indicated in our histopathology results, respectively. There are various mechanisms by which CoQ serves lipid metabolism such as boosting fatty acid oxidation and inhibiting the oxidation of low-density lipoprotein, the primary carrier of blood cholesterol, which is implicated in the cumulation of cholesterol (Gutierrez-Mariscal et al, 2020).…”
Section: Discussionsupporting
confidence: 61%
“…The GC/MS chromatogram revealed that saponin, terpenoids, steroids, oleic acid, fatty acids methyl esters, vitamin A, and glyceryl palmitate were the most ubiquitous constituents in the TM seed extract ( Table 1 ). Notably, these secondary metabolites evince diverse therapeutic potential, mainly antioxidant ( S et al, 2021 ; Atawodi et al, 2013 ), anti-inflammatory ( Mushtaq et al, 2021 ), and antihyperlipidemic ( Velu et al, 2018 ) properties. The presence of these phytochemicals is in congruence with that reported in preceding studies those screened the prime constituents of T. indica seeds ( S et al, 2021 ; Mushtaq et al, 2021 ; Sadiq et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The seed oil resembles that of groundnut oil which is thrown as waste. Tamarind seed oil was found to contain carbohydrates (50-55%), tannins (20%), fiber (12-20%) and oil (4.5-16.2%) [11]. However, the seeds were found to be unsuitable for human consumption due to the presence of tannins and others toxic chemicals.…”
Section: Introductionmentioning
confidence: 99%